2023
DOI: 10.1038/s41593-023-01338-z
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human prediction of chronic pain state using intracranial neural biomarkers

Abstract: Chronic pain syndromes are often refractory to treatment and cause substantial suffering and disability. Pain severity is often measured through subjective report, while objective biomarkers that may guide diagnosis and treatment are lacking. Also, which brain activity underlies chronic pain on clinically relevant timescales, or how this relates to acute pain, remains unclear. Here, four participants with refractory neuropathic pain were implanted with chronic intracranial electrodes in the anterior cingulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 57 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Some studies suggest that OFC may inhibit pain by participating in reward-related circuits (Rolls, 2023) and connecting to subcortical centers like the periaqueductal gray involved in pain modulation (Huang et al, 2021). Additionally, Shirvalkar et al ( 2023) recently reported that OFC signals could be used in predicting chronic pain (Shirvalkar et al, 2023). However, animal and human data on the OFC's role in pain and TTH mechanisms remain limited, necessitating further research to elaborate on its contributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that OFC may inhibit pain by participating in reward-related circuits (Rolls, 2023) and connecting to subcortical centers like the periaqueductal gray involved in pain modulation (Huang et al, 2021). Additionally, Shirvalkar et al ( 2023) recently reported that OFC signals could be used in predicting chronic pain (Shirvalkar et al, 2023). However, animal and human data on the OFC's role in pain and TTH mechanisms remain limited, necessitating further research to elaborate on its contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Shirvalkar et al. (2023) recently reported that OFC signals could be used in predicting chronic pain (Shirvalkar et al., 2023). However, animal and human data on the OFC's role in pain and TTH mechanisms remain limited, necessitating further research to elaborate on its contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, ML and EEG remain promising for pain classification, but improved performance from robustly designed studies remains imperative. Finally, whilst continuous pain intensity prediction is desirable for finer prediction resolution which would enable improved pain assessment and treatment monitoring/recommendations (Shirvalkar et al, 2023), it appears unrealistic within the current approach.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining more precise pain estimates may enable improved pain management. For example, predicting continuous ratings enables finer monitoring of pain over time and allows for changes after treatment to be more accurately assessed (e.g., small changes in pain intensity can be identified, which is not possible with broad binary classification; Shirvalkar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The MED can also help extend multimodal motor BCIs to naturalistic setups where task-related events, such as movement onset, must be detected before decoding is possible. In addition to spiking and LFP, the application of MED to other neural modalities such as intracranial EEG or electrocorticography, which have high potential for translation, is also an important future direction [22,74,75,[84][85][86][87][88][89][90][91][92][93][94][95][96]. Finally, the combination of MED with various learning algorithms for neural population modeling and decoding, even in the presence of external input stimuli (e.g.…”
Section: Applications and Future Directionsmentioning
confidence: 99%